Spatiotemporal long-term wind and storm characteristics over the eastern Mediterranean Sea - Gumuscu, Irem; Islek, Fulya; Yuksel, Yalcin; Sahin, Cihan (ELSEVIER, 2023)
The main objective of the present study is to provide a comprehensive analysis of wind characteristics over the eastern Mediterranean Sea using three widely used wind fields, namely ECMWF ERA-Interim, ECMWF ERA5, and NCEP/CFSR. Wind speeds from three reanalysis datasets were validated with measurements at three different locations (Antalya, Dardanelles, and Silifke). The results of several statistical investigations show that ERA5 and CFSR wind data provide reasonably better fits with measurements compared to results of ERA-Interim data, especially in higher percentiles. Long-term wind and storm characteristics, long-term variability, and long-term trends with statistical significance levels were evaluated covering the period of 1979-2018. Long-term strong wind conditions with no significant long-term trend were detected in the northern Aegean Sea, while relatively weak, short-lived, and highly variable winds were determined in the southern, northern, and eastern Levantine Basin. For five selected regions, local analyses such as storm duration, and 99th percentile wind speed were evaluated in detail. Extreme wind analyses indicate that the largest discrepancy between the results of ERA5 and CFSR wind datasets was observed in the eastern Levantine basin, with the RC (relative difference) exceeding 22%. The highest extreme wind speeds for the 100-year return period were found in the northern Aegean Sea with values exceeding 21 m/s and 25 m/s for ERA5 and CFSR, respectively. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: ERA-interim; ERA5; CFSR; Wind characteristics; Long-term changes; Spatiotemporal variability; Eastern Mediterranean Sea; REANALYSIS; CLIMATE; INTERIM; MODEL; Environmental Sciences & Ecology; Marine & Freshwater Biology